2001
DOI: 10.1046/j.1440-169x.2001.00550.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulating potential in development of a direct developing echinoid, Peronella japonica

Abstract: The regulating potential along the animal-vegetal axis of a direct developing echinoid, Peronella japonica, was investigated using LiCl. Animal caps isolated from 16-cell stage P. japonica embryos developed to permanent blastulae with an amniotic cavity. Treatment of animal caps with LiCl induced them to vegetalize with differentiation of the endoderm and subsequently develop into pluteus-like larvae. The larvae derived from the LiCl-treated animal caps were able to metamorphose and establish an adult body pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…LiCl (Kitazawa & Amemiya 2001 & references therein) A23187 (calcium) (Lane et al . 1993;Akasaka et al .…”
Section: Gastrulationmentioning
confidence: 99%
“…LiCl (Kitazawa & Amemiya 2001 & references therein) A23187 (calcium) (Lane et al . 1993;Akasaka et al .…”
Section: Gastrulationmentioning
confidence: 99%
“…However, the mechanism of the effect of LiCl on the establishment of LR asymmetry is still unclear. This study showed that LiCl impairs LR asymmetry around the period between the 16-cell and blastula stage, which includes the periods sensitive to the induction of vegetalization (around the 64-to 512-cell stage) shown by Kitazawa and Amemiya (2001) in this species. In the next step, it will be important to determine whether the molecular pathway affected by LiCl that results in the establishment of LR asymmetry is coupled with the pathway for vegetalization.…”
Section: Effect Of Licl On the Lr Asymmetry Of Echinoid Larvaementioning
confidence: 65%
“…This effect of vegetalization, however, had been studied in only indirect developers, and no reports had suggested that LiCl influences the establishment of LR asymmetry in echinoids. We recently investigated the effect of LiCl on a directdeveloping echinoid, P. japonica, and found that LiCl generally causes evagination of invaginating tissues, including both the amniotic cavity and the archenteron (Kitazawa and Amemiya, '97, 2001), and that LiCl causes the embryos to radialize (Kitazawa and Amemiya, 2001).…”
Section: Introductionmentioning
confidence: 99%